Culture and heritage for a just transition to climate-neutral and smart cities. Text mining supporting New European Bauhaus elements detection - Costanzo, Ezilda; Alderuccio, Daniela (Frontiers in Sustainable Energy Policy, 2025)
Cities are at the forefront in linking their socio-economic development to culture and heritage that they are slowly acknowledging as a way to also address climate change. Cultural participation can influence a diverse range of social impact areas, such as health and wellbeing, social cohesion and intercultural dialogue, innovation, and education, as well as community-driven urban and territorial renewal and development. The sense of heritage ownership is a complex relationship between individual, collective, and institutional claims that can leverage action and better governance. With the New European Bauhaus (NEB) initiative launched in 2021, the European Union pledges culture's contribution to the European Green Deal and advocates the role of cultural institutions, as they play a vital role in strengthening community engagement. This article illustrates to what extent culture (arts, heritage, cultural, and creative industries) and NEB principles are mainstreamed into recent and innovative urban energy and climate policies to drive behavioral change and improve networking and multi-stakeholder commitment. We have focused on a sample of the 100 EU Mission Cities. By analyzing their road maps for climate-neutrality and smartness, the Climate City Contracts (CCCs), we have addressed the following questions: – Do cities rely on culture and heritage for a just transition? – What is the role of arts, heritage, cultural, and creative Industries in their pathways for a just transition? – Do these actions take advantage of digitalization? Based on the vocabulary categorization, we have started developing a text mining method that may support extending the analysis of “culture for climate action”—related elements to a broader number and types of urban transition policies. We have interpreted the CCCs sample providing a high-quality human-annotated corpus. The aim is to train a future artificial intelligence model that could help assess impacts and identify other culture and heritage-based experiences to enhance “Knowledge for Policy” toward the NEB application in cities.